La Conferencia de Chapultepec (1945): El nacionalismo económico latinoamericano frente a la política librecambista de Estados Unidos - José Galindo (América Latina en la Historia Económica, 2017)
The present article seeks to illustrate the change of economic model in Latin America from the crisis of 1929 and the transition from the model focused “outwards” to the “internal market”, using mainly the case of Mexico. It will also explain the effects of the Second World War on the major Latin American economies and the emergence of explicit industrialization policies in these countries. Based on the analysis of primary and secondary sources, the so-called Chapultepec Conference (1945) will be examined, with an emphasis on the structure of debate and contrast in the positions of Latin American countries, interested in maintaining and expanding economic nationalism and its processes of industrialization, which managed to moderate the free-trade economic proposals promoted by the United States